Bioindicators and bioclimatic data as essential tools towards a consistent biogeographic district typology of Sierra Nevada National Park (Spain) - Marfil, Jose Miguel; Molero, Joaquín; Cantó, Paloma; Rivas-Martínez, Salvador (Lazaroa, 2017)
The relationship, through the application of robust and solvent bioclimatic indexes, between the characteristics of the natural environment (geology, orography, climate, et.) and the recognition of species, communities and vegetation series, has made it possible to establish in the Sierra Nevada National Park (Spain) a total of 8 homogeneous spaces (districts), included in other larger spaces (5 sectors, 2 provinces), which constitute the biogeographic typology of the territory. The consideration, inter alia, of historical climatic changes and human action show the necessary use of phytosociological methodology in the characterization of species, communities and vegetation series. The application of the Aridic Index and the positive temperature, in the bioclimatic context, explains the generalized aridity in the territory and the apparent contradiction of spaces with dry and semiarid ombroclima in the highest summits. The recognition of homogeneous territories (districts), is an essential tool for the management of the National Park.